Captured landscape : the paradox of the enclosed garden - Baker, Kate, 1949- (New York : Routledge, 2012)
The enclosed garden, or hortus conclusus, is a place where architecture, architectural elements, and landscape, come together. It has a long history, ranging from the paradise garden and cloister, the botanic garden and the giardini segreto, the kitchen garden and the stage for social display, to its many modern forms; the city retreat, the redemptive garden, and the deconstructed building. By its nature it is ambiguous. Is it an outdoor room, or captured landscape; is it garden or architecture? Kate Baker discusses the continuing relevance of the typology of the enclosed garden to contemporary architects by exploring influential historical examples alongside some of the best of contemporary designs -- brought to life with vivid photography and detailed drawings -- taken mainly from Britain, the Mediterranean, Japan and South America. She argues that understanding the potential of the enclosed garden requires us to think of it as both a design and an experience. As climate change becomes an increasingly important component of architectural planning, the enclosed garden, which can mediate so effectively between interior and exterior, provides opportunities for sustainable design and closer contact with the natural landscape. Study of the evolution of enclosed gardens, and the concepts they generate, is a highly effective means for students to learn about the design requirements of outdoor space proximal to the built environment. Captured Landscape provides architectural design undergraduates, and practising architects, with a broad range of information and design possibilities. It will also appeal to landscape architects, horticulturalists and a wider audience of all those who are interested in garden design.
Defining the territory : the ambiguous nature of an enclosed garden -- From patio to park: the enclosed garden as a generator of architectural and landscape design -- Taming nature - and the way to paradise -- Ritual and emptiness - and the rigour of developing an idea -- Sensory seclusion : the affective garden, the garden room as a scene for living -- Detachment : the separation of the garden from the building.
Includes bibliographical references (p. [195]-198) and index.
Keywords: Geschichte; Landscape design; Gardens -- Design